2021
DOI: 10.1016/j.jcis.2020.07.147
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected thermo-responsiveness of bisurea-functionalized hydrophilic polymers in water

Abstract: Hypothesis: Thermoresponsive polymers are important materials for various applications. However, the number of polymers that exhibit this property in the temperature range of interest remains limited. The development of novel rational design strategies through the understanding of the thermal transition's origin is therefore of utmost importance. Experiments: Bisurea-functionalized water-soluble polymers were synthesized by RAFT polymerization. After direct dissolution in water, the supramolecular assemblies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…In contrast, solutions of more hydrophilic P8‐6 OMe and P12‐10 OMe remained transparent up to 80°C, the highest temperature measured (Figure 3(B)). We can conclude that the LCST behavior of OEG amphiphiles is strongly related to hydrophilic/hydrophobic balance, and more hydrophobic amphiphiles have lower LCST's, in line with observations of thermo‐induced aggregation in bis‐urea functionalized supramolecular bottlebrushes system 40 …”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…In contrast, solutions of more hydrophilic P8‐6 OMe and P12‐10 OMe remained transparent up to 80°C, the highest temperature measured (Figure 3(B)). We can conclude that the LCST behavior of OEG amphiphiles is strongly related to hydrophilic/hydrophobic balance, and more hydrophobic amphiphiles have lower LCST's, in line with observations of thermo‐induced aggregation in bis‐urea functionalized supramolecular bottlebrushes system 40 …”
Section: Resultssupporting
confidence: 89%
“…We can conclude that the LCST behavior of OEG amphiphiles is strongly related to hydrophilic/hydrophobic balance, and more hydrophobic amphiphiles have lower LCST's, in line with observations of thermo-induced aggregation in bis-urea functionalized supramolecular bottlebrushes system. 40 Dynamic light scattering (DLS) was subsequently used to study aggregate behaviors in more detail. Bolaamphiphiles with apolar segments larger than 10 carbon atoms may form non-equilibrium aggregates, and the kinetics of exchange are further slowed down by hydrogen bonding of urea motifs.…”
Section: Characterization In Aqueous Solutionmentioning
confidence: 99%
“…Finally, at both sample concentrations (0.1 and 1 wt%), the initial size of the small aggregates was recovered when the samples were cooled back to 20 °C; the transition is thus reversible (Figure S10) as already indicated by turbidimetry. In view of theses combined analyses, the apparent LCST-type transition, might therefore be explained by the destabilization of the colloidal system [27]. At both concentrations, upon heating from 20 to 70 °C, the initial aggregates form larger aggregates through a secondary aggregation mechanisms, which are nanometric and remain colloidally stable at 0.1 wt%, but become micrometric and colloidally unstable at 1 wt%.…”
Section: Thermoresponsive Behaviormentioning
confidence: 95%
“…This specific interaction led to a significant salting-in effect (increasing LCST), competing with the typical salting-out effect (decreasing LCST), which could nearly restore the original LCST (27.9 1C compared to 30.2 1C of the salt-free LCST). 117 A couple of examples also revealed that by modifying a polymer with moieties that are prone to cause intermolecular non-covalent interactions, such as boronic acid 118 and urea, 119,120 could be applied for introducing and optimizing the range of thermoresponsiveness. It was illustrated that introduction of a bis-urea terminal group to poly(N,N-dimethylacrylamide) (PDMAc) enabled the temperature-sensitive characteristic to the polymer.…”
Section: Manipulation Of Non-covalent Interactionsmentioning
confidence: 99%
“…It was explained that the bis-urea terminal facilitated the hydrogen bond formation intermolecularly, causing stronger inter-chain interactions and temperature sensitivity. 120 Universally, polymers with pendant groups have been studied for thermoresponsive applications. These polymers benefit from modulation of responsive temperature range by simply changing monomer structures, polymer composition, and degree of polymerization.…”
Section: Manipulation Of Non-covalent Interactionsmentioning
confidence: 99%